MRP8/14 induces autophagy to eliminate intracellular Mycobacterium bovis BCG. Issue 4 (April 2015) - Wang, Jinli; Huang, Chunyu; Wu, Minhao; Zhong, Qiu; Yang, Kun; Li, Miao; Zhan, Xiaoxia; Wen, Jinsheng; Zhou, Lin; Huang, Xi
Summary Objective To explore the role of myeloid-related protein 8/14 in mycobacterial infection. Methods The mRNA and protein expression levels of MRP8 or MRP14 were measured by real-time PCR and flow cytometry, respectively. Role of MRP8/14 was tested by overexpression or RNA interference assays. Flow cytometry and colony forming unit were used to test the phagocytosis and the survival of intracellular Mycobacterium bovis BCG (BCG), respectively. Autophagy mediated by MRP8/14 was detected by Western blot and immunofluorescence. The colocalization of BCG phagosomes with autophagosomes or lysosomes was by detected by confocal microscopy. ROS production was detected by flow cytometry. Results MRP8/14 expressions were up-regulated in human monocytic THP1 cells and primary macrophages after mycobacterial challenge. Silencing of MRP8/14 suppressed bacterial killing, but had no influence on the phagocytosis of BCG. Importantly, silencing MRP8/14 decreased autophagy and BCG phagosome maturation in THP1-derived macrophages, thereby increasing the BCG survival. Additionally, we demonstrated that MRP8/14 promoted autophagy in a ROS-dependent manner. Conclusions The present study revealed a novel role of MRP8/14 in the autophagy-mediated elimination of intracellular BCG by promoting ROS generation, which may provide a promising therapeutic target for tuberculosis and other intracellular bacterial infectious diseases.